Correction: Point Pattern Analysis (PPA) as a tool for reproducible archaeological site distribution analyses and location processes in early iron age south-west Germany. - Giacomo Bilotti; Michael Kempf; Eljas Oksanen; Lizzie Scholtus; Oliver Nakoinz (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0297931.].